Campath induction in HCV and HCV/HIV‐seropositive kidney transplant recipients. (16th August 2013) - Vivanco, Marcelo; Friedmann, Patricia; Xia, Yu; Klair, Tarunjeet; Marfo, Kwaku; de, Graciela; Greenstein, Stuart; Chapochnick‐Friedmann, Javier; Kinkhabwala, Milan; Ajaimy, Maria; Lubetzky, Michelle L.; Akalin, Enver; et al.
Summary Alemtuzumab (AZ) induction in hepatitis C‐seropositive (HCV+) kidney transplant (KTX) recipients may negatively affect patient survival; however, available information is scant. Using US registry data from 2003 to 2010 of adult HCV+ deceased‐donor KTXs (n = 4910), we examined outcomes by induction agent – AZ (n = 294), other T cell‐depleting agents, (n = 2033; T cell), IL‐2 receptor blockade (n = 1135; IL‐2RAb), and no induction (n = 1448). On multivariate analysis, induction therapy was associated with significantly better overall patient survival with AZ [adjusted hazards ratio (aHR) 0.64, 95% confidence interval (CI) 0.45, 0.92], T cell (aHR 0.52, 95% CI 0.41, 0.65) or IL‐2RAb (aHR 0.67, 95% CI 0.53, 0.87), compared to no induction. A significant protective effect was also seen with AZ (aHR 0.63, 95% CI 0.40, 0.99), T cell (aHR 0.62, 95% CI 0.49, 0.78), and IL2R‐Ab (aHR 0.62, 95% CI 0.47, 0.82) in terms of death‐censored graft survival relative to no induction. There were 88 HIV+/HCV+ coinfected recipients. Compared to noninduction, any induction (i.e. three induction groups combined) was associated with similar overall patient survival (P = 0.2255) on univariate analysis. Induction therapy with AZ, other T cell‐depleting agents, or IL‐2RAb in HCV+ KTX is associated with better patient and death‐censored graft survival compared to noninduction. In HCV/HIV coinfected patients, induction is not contraindicated.